Developing the Language Pragmatic Competence in Children With Moderate and Severe Mental Disorders - Bethere, Dina; Roste–Plostniece, Inese; Žīmante, Kaiva (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
In this research the effectiveness of didactic system is analysed in relation to forming communicative competence of children with moderate and severe mental disorders (MSMD) in the older classes. This publication presents the language competency model, which in this research serves as a theoretical base for studying the language development of pupils and for pedagogical activity. The publication reveals the system of methodological approaches in the educational process for developing pragmatic language competency for pupils with MSMD.